PREFACE - Kurakbayev, Kairat; Sagintayeva, Aida (My University, 2016)
Chapters presented in these proceedings shed light on global and local nuance of developing academic entrepreneurship. The authors invite the reader to take part in the discussion of eminent challenges and reflect on long-term issues of building an innovative and entrepreneurial university. It is hoped that these proceedings will be valuable to university leaders, faculty, graduate students and other stakeholders who have to interact with higher education institutions. Nation-specific chapters on Kazakhstan could be useful to scholars who research developments of higher education in this region.
Keywords: The fifth Eurasian Higher Education Leaders’ Forum; Higher Education